Herbicide Resistance in Plants - Beckie, Hugh J. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Today, herbicide-resistant weeds dominate research and development efforts in the discipline of weed science. The incidence, management challenges, and cost of multiple herbicide-resistant weed populations are continually increasing worldwide. Crop varieties with multiple herbicide-resistance traits are being rapidly adopted by growers and land managers to keep ahead of the weed resistance tsunami. This Special Issue of Plants comprises papers that describe the current status and future outlook of herbicide resistance research and development in weedy and domestic plants, with topics covering the full spectrum from resistance mechanisms to resistance management. The unifying framework for this Special issue is the challenge posed to all of the contributing authors: What are the (potential) implications for herbicide resistance management?